In-situ surface modification method for enhancing poison resistance of high-density metal-based hydrogen storage alloy

The nitride protective layer is formed on the ZrCo-based alloy by in-situ surface modification method, which solves the problem of slowing down its hydrogen absorption rate in high-temperature ablation and impurity gases, and achieves efficient and economical anti-toxicity performance improvement, suitable for hydrogen Isotope storage and supply.

CN119287285AActive Publication Date: 2025-01-10ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411415626.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

During the ITER operation, ZrCo-based alloys have slowed down the hydrogen absorption rate and even lost activity due to high-temperature ablation and mixed impurity gases, which affects its application in the field of hydrogen isotope storage. The existing modification methods are complex and costly, and it is difficult to effectively improve. Antitoxic properties.

Method used

Using in-situ surface modification method, the activated dehydrogenated ZrCo-based alloy is insulated at 350-450°C in the H2+ modification gas mixture for surface modification. Inexpensive modification gases such as N2 and CO2 are used to form a dense and uniform nitride protective layer, which is significantly Enhance the anti-CO2 and CO toxicity properties of the alloy.

Benefits of technology

It simply and efficiently improves the anti-CO2 and CO toxicity properties of ZrCo-based alloy, significantly enhances the hydrogenation reaction activity, extends the service life of the alloy, reduces the modification cost, and is suitable for the storage, supply and recycling of hydrogen isotopes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287285A_ABST
    Figure CN119287285A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ surface modification method for enhancing CO2 and CO poisoning resistance of a high-density metal-based alloy. The in-situ surface modification method comprises the following steps: 1) carrying out surface modification on an activated and dehydrogenated ZrCo-based alloy in H2 + modification gas mixture at 350-450 DEG C; the modification gas is at least one of N2 and CO2; and 2) cooling the alloy treated in the step 1) under a dynamic evacuation condition to obtain the ZrCo-based alloy with CO2 and CO poisoning resistance. A modification strategy of in-situ surface reconstruction is adopted, and the problem that the ZrCo-based alloy is poor in CO2 and CO poisoning resistance is solved. The method is simple in step, low in cost and high in safety, and has important significance in promoting application and popularization of the ZrCo-based alloy in the field of hydrogen energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen isotope storage and supply technology, and in particular to a high-density ZrCo metal-based hydrogen storage alloy that is resistant to carbon dioxide (CO 2 ), in situ surface modification method for carbon monoxide (CO) poisoning performance. Background Art

[0002] Deuterium-tritium controlled nuclear fusion technology is one of the main ways to obtain clean energy in the future. During the operation of a nuclear fusion reactor, the safe, stable and efficient supply of deuterium-tritium fuel to the fuel filling system is the key to ensuring the stable operation of the reactor. With the advancement of nuclear fusion projects such as ITER (International Thermonuclear Experimental Reactor), the recovery, storage and supply technology of hydrogen isotopes has become an important research direction. In particular, the technical challenges for the management of tritium, a radioactive isotope, are particularly significant. Tritium is not only radioactive, but also scarce in resources. Therefore, its efficient recovery and safe storage have become important issues to ensure the sustainable development of nuclear fusion energy. By adopting high-density metal-based hydrogen storage materials with specific thermodynamic and kinetic properties, safe storage and precise supply of hydrogen isotopes can be achieved. High-density ZrCo metal-based alloy materials have a low hydrogen absorption platform pressure (about 10 -3 Pa), and can achieve efficient absorption of hydrogen isotopes at lower pressures. In addition, its hydrogen absorption and desorption kinetics are fast, and the hydrogen absorption and desorption reactions can be completed in a short time, meeting the dynamic demand of fusion reactors for hydrogen isotopes. More importantly, ZrCo alloys are non-radioactive, have high safety in use, and have a low risk of spontaneous combustion. They have good helium fixing performance and are suitable for use in environments with high safety requirements such as nuclear fusion reactors. Therefore, ZrCo alloys have become an important candidate material in hydrogen isotope storage and supply systems, and have broad application prospects.

[0003] However, ZrCo alloys also encounter some problems in practical applications. For example, during the operation of ITER, due to the high temperature generated by the deuterium-tritium fusion reaction, the CO 2 Impurity gases such as CO will inevitably be mixed in the hydrogen isotope gas. The presence of these oxygen-containing impurity gases will seriously slow down the hydrogen absorption rate of ZrCo-based alloys. When the impurity gas content reaches a certain level, the hydrogen storage alloy will even completely lose its activity, thus affecting the application of ZrCo-based alloys in the field of ITER hydrogen isotope storage. Therefore, it is necessary to develop an effective surface modification method for ZrCo-based alloys to improve the alloy's anti-poisoning ability and thus extend its service life.

[0004] In order to improve the anti-poisoning performance of ZrCo-based alloys, researchers have proposed several solutions. For example, Zhejiang University used ZrCo alloys in CO 2 H of impurity gas2 The ZrCo alloy undergoes multiple cycles of hydrogen absorption and desorption, thereby in situ homogeneously constructing Co nanoparticles with high catalytic activity for hydrogenation reactions on its surface, thereby improving the ZrCo alloy's resistance to CO. 2 Poisoning ability (a method for enhancing the anti-carbon dioxide poisoning performance of ZrCo alloy, patent number: ZL202211727886.0). However, this method requires that the ZrCo alloy be subjected to multiple hydrogen absorption and desorption cycles in the mixed gas to achieve the ideal anti-poisoning effect. The process is relatively complicated, and as the hydrogen absorption and desorption cycles proceed, the ZrCo alloy will inevitably react with H 2 and CO 2 Disproportionation and oxidation reactions occur, resulting in a continuous decrease in hydrogen storage capacity during the modification process. 2 Wrapped on the surface of ZrCo alloy, it improves the alloy's resistance to CO and CO 2 and air poisoning ability (enhancing ZrCo alloy resistance to CO, CO 2 , air poisoning and anti-powdering performance, patent number: ZL201410532678.4); Beijing Nonferrous Metals Research Institute modified the surface of ZrCo alloy with Pd or Pd-Ag chemical plating, and found that the PdAg / ZrCo alloy after the protective layer was plated with CO, CO 2 The ability of impurity gases such as Pd / Ag is increased. However, the above process also has some shortcomings. It needs to adopt a complex process of heterogeneously coating other metal elements on ZrCo, and these coated metal elements themselves cannot effectively store hydrogen and are also prone to alloying reactions with Zr or Co elements, resulting in a decrease in the actual mass hydrogen storage capacity of the sample, thereby increasing the difficulty and uncertainty of preparing the sample. At the same time, this non-in-situ grown coating layer is not tightly combined with ZrCo, and is easy to fall off during the recycling process, causing the anti-poisoning performance to decrease. In addition, the cost of Pd / Ag is also high, which is not conducive to large-scale promotion and application. In order to further improve the anti-poisoning performance of ZrCo-based alloys, it is necessary to develop a more concise, efficient and cost-controlled in-situ surface modification method. Summary of the invention

[0005] In view of the above technical problems and the shortcomings in the art, the present invention provides a high-density ZrCo-based hydrogen storage alloy with enhanced CO resistance. 2 The in-situ surface modification method for improving the CO poisoning performance can solve the problem that ZrCo-based hydrogen isotope storage alloys generally have poor anti-poisoning performance. The hydrogen isotopes described in the present invention include one or more of protium, deuterium and tritium.

[0006] An enhanced high-density ZrCo metal-based hydrogen storage alloy against CO 2 , an in-situ surface modification method for improving CO poisoning performance, comprising the steps of:

[0007] 1) The activated dehydrogenated ZrCo-based alloy is heat-preserved at 350 - 450 °C (such as 430 °C, etc.) in a mixed gas of H 2 + and a modifying gas for surface modification; the modifying gas is N 2 , CO 2 or at least one of them;

[0008] 2) Under dynamic evacuation conditions, the alloy treated in step 1) is cooled to obtain a ZrCo-based alloy with resistance to CO 2 and CO poisoning properties.

[0009] In step 1), the ZrCo-based alloy can be a ZrCo alloy partially substituted or unsubstituted by one or more transition metal elements, and the transition metal elements can be selected from Cu, Ni, Hf, Ti, Nb.

[0010] In step 1), the ZrCo-based alloy can be a ZrCo alloy, ZrCo (1-a) Cu a alloy, ZrCo (1-b) Ni b alloy, Zr (1-c) Hf c Co alloy, Zr (1-d) Ti d Co alloy or Zr (1-e) Nb e Co alloy, where 0 < a < 0.4 (such as 0.2, etc.), 0 < b < 0.4 (such as 0.2, etc.), 0 < c < 0.4 (such as 0.2, etc.), 0 < d < 0.4 (such as 0.2, etc.), 0 < e < 0.4 (such as 0.2, etc.).

[0011] In step 1), the activated dehydrogenated ZrCo-based alloy can be obtained in the following way:

[0012] The ZrCo-based alloy ingot is dynamically evacuated at 400 - 500 °C to remove the impurity gases on the surface of the ZrCo-based alloy ingot; after the evacuation ends, when the temperature drops below 200 °C, hydrogen is filled to make the surface-degassed ZrCo-based alloy ingot absorb hydrogen and be activated, and then the temperature is raised to 500 - 550 °C, and the hydrogen-absorbed and activated ZrCo-based alloy is dynamically evacuated for dehydrogenation to obtain the activated dehydrogenated ZrCo-based alloy.

[0013] In step 1), the heat-preservation time at 350 - 450 °C can be 3 - 30 min, such as 5 min, 10 min, 15 min, etc.

[0014] In step 1), the introduced H 2+ The initial back pressure of the modified gas mixture can be 0.5-4.0 bar, such as 1.2 bar.

[0015] In step 1), the H 2 + The content of the modified gas in the modified gas mixture may be 1 mol%-10 mol%, such as 5 mol%. The remainder may be H 2 .

[0016] The present invention also provides a CO 2 , CO poisoning resistance ZrCo-based alloy can be prepared by the in-situ surface modification method. 2 , the CO poisoning performance of ZrCo-based alloys indicates that a dense and uniform protective layer is generated, and the material of this protective layer can be nitride, etc.

[0017] The present invention also provides the anti-CO 2 The invention relates to an application of a ZrCo-based alloy with low CO poisoning performance in the storage, supply and recovery of hydrogen isotopes. The hydrogen isotopes may include one or more of protium, deuterium and tritium.

[0018] The present invention adopts the modification strategy of in-situ surface reconstruction to solve the problem of ZrCo-based alloy's resistance to CO 2 , and poor CO poisoning ability. The modified ZrCo-based alloy has poor CO 2 and / or CO impurity gas H 2 The hydrogenation reaction activity in the mixed gas is significantly enhanced.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The method of in-situ surface modification of high-density ZrCo-based alloys of the present invention belongs to in-situ homogeneous modification. All operations can be completed in a single hydrogen absorption and desorption system, without the need for additional heterogeneous coating modification processes, thereby avoiding the complexity of sample transportation in different process steps and a series of problems such as oxidation and contamination.

[0021] 2. The process flow of the present invention is very simple and easy to operate, and only one modification is needed to achieve the desired effect. Compared with the unmodified ZrCo-based alloy, the surface of the ZrCo-based alloy modified by the present method can significantly enhance the H- 2 +CO 2 CO resistance of alloys when absorbing hydrogen in CO / CO mixture 2 , CO poisoning performance, thereby effectively improving the hydrogenation reaction activity of ZrCo-based alloys, which is particularly suitable for hydrogen isotope storage, supply and recovery for ITER.

[0022] 3. The present invention greatly reduces the cost of modification, and the raw materials used are cheap N 2 , CO 2 It avoids the use of expensive heterogeneous coating materials, has simple steps, high safety, and can be used in CO 2 The results show that the ZrCo-based alloys are still applicable in hydrogen isotope scenarios with CO impurities, which is of great significance for promoting the application and promotion of ZrCo-based alloys in the field of hydrogen isotope storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The invention discloses a high-density ZrCo metal-based alloy that is resistant to CO 2 , schematic flow chart of the in situ surface modification method for CO poisoning performance.

[0024] Figure 2 ZrCo (ZC) containing 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0025] Figure 3 Zr 0.8 Hf 0.2 Co(ZHC) contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0026] Figure 4 Zr 0.8 Nb 0.2 Co(ZNC) containing 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0027] Figure 5 Zr 0.8 Ti 0.2 Co(ZTC) contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0028] Figure 6 ZrCo 0.8 Ni 0.2 (ZCN) contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0029] Figure 7 ZrCo 0.8 Cu 0.2 (ZCC) contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0030] Figure 8 ZrCo and ZrCo at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZC-N) after surface modification for 5-30 minutes in the mixed gas contains 2000ppm CO at 10bar 2 H 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0031] Fig. 9 ZrCo and ZrCo at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%CO 2 The sample after surface modification for 5-30 minutes in the mixed gas contains 2000ppm CO at 10bar 2 H 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0032] Fig.10 ZrCo (ZC) and ZrCo at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZC-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0033] Fig.11 Zr 0.8 Hf 0.2 Co(ZHC) and Zr 0.8 Hf 0.2 Co at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZHC-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics curve in mixed gas.

[0034] Fig.12 Zr0.8 Nb 0.2 Co(ZNC) and Zr 0.8 Nb 0.2 Co at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZNC-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0035] Fig.13 Zr 0.8 Ti 0.2 Co(ZTC) and Zr 0.8 Ti 0.2 Co at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZTC-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0036] Fig.14 ZrCo 0.8 Ni 0.2 (ZCN) and ZrCo 0.8 Ni 0.2 At 430 °C, 1.2 bar 95 mol% H 2 +5mol%N 2 The sample (ZCN-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0037] Fig.15 ZrCo 0.8 Cu 0.2 (ZCC) and ZrCo 0.8 Cu 0.2 At 430 °C, 1.2 bar 95 mol% H 2 +5mol%N 2 The sample (ZCC-N) after surface modification for 10 minutes in the mixed gas contains 2000ppm(a)CO at 10bar 2 or (b) H of CO 2 Room temperature hydrogen absorption kinetics in mixed gases.

[0038] Fig.16 ZrCo, ZrCo at 430 °C, 1.2 bar, 95 mol% H 2 +5mol%N 2 Sample (ZC-N) after surface modification for 10 minutes in mixed gas and 2000ppm CO after modification at 10 bar 2 H 2 X-ray diffraction (XRD) analysis results of the sample (ZC-NH) after saturation of hydrogen absorption in the mixed gas at room temperature.

[0039] Fig.17 For ZrCo at 430 °C, 1.2 bar 95 mol% H 2 +5mol%N 2 Transmission electron microscopy photograph of the sample (ZC-N) after surface modification in mixed gas for 10 minutes.

[0040] Fig.18 For ZrCo and ZrCo at 430 °C, 1.2 bar 95 mol% H 2 +5mol%N 2 PCT (pressure-composition-temperature curve) test results of hydrogen absorption / desorption of the sample (ZC-N) after surface modification for 10 minutes in the mixed gas. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0042] The present invention is mainly used for surface modification of high-density ZrCo metal-based alloys to enhance their CO resistance. 2 , CO poisoning performance.

[0043] like Figure 1 As shown in the figure, the process flow of the present invention for modifying high-density ZrCo metal-based alloy powder can be divided into: (1) preparing an activated dehydrogenated ZrCo-based alloy; (2) introducing 0.5-4.0 bar of 1-10 mol% N at 350-450°C; 2 or CO 2 H 2 mixed gas; (3) heat preservation for 3-30min to carry out surface non-metallic modification; (4) cool to room temperature under dynamic vacuum conditions to obtain CO2 resistant 2 , modified samples with significantly improved CO poisoning ability.

[0044] Comparative Example 1:

[0045] Weigh Zr and Co with equal atomic ratios and perform magnetic levitation induction melting to obtain a ZrCo alloy ingot with uniform composition. The surface oxide film of the smelted ZrCo alloy is polished off with a grinding wheel, and then the ingot is placed in a reactor, dynamically evacuated at 500℃ for 1h, and then cooled to 100℃ for insulation. Then 20bar high-purity H 2 The activated ZrCoH was absorbed for 10 h. 3 powder.

[0046] The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550° C. and kept warm for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining an activated dehydrogenated ZrCo alloy.

[0047] At room temperature, 10 bar of 2000 ppm CO was introduced into the activated dehydrogenated ZrCo alloy. 2 or H of CO 2 Mixed gas, measure the hydrogen absorption kinetic curve of ZrCo in the mixed gas. Figure 2 As shown, in H 2 +CO 2 In the mixed gas, the material can absorb 0.53wt% hydrogen within 20min; 2 In the mixed gas of 100 % CO and 40 % CO, the time required for the material to absorb 0.7 wt% hydrogen is 84.3 min.

[0048] Comparative Example 2:

[0049] Weigh Zr, Hf and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Hf 0.2 Co alloy ingot. 0.8 Hf 0.2 The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Hf 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Hf 0.2 Co alloy.

[0050] At room temperature, the activated dehydrogenated Zr 0.8 Hf 0.2 Co alloy introduced into 10 bar containing 2000 ppm CO 2 or H of CO2 Mixed gas, measuring Zr 0.8 Hf 0.2 The kinetic curve of hydrogen absorption of Co in mixed gas. Figure 3 As shown, in H 2 +CO 2 and H 2 +CO mixed gas, the time required for the material to absorb 0.7wt% hydrogen is 6.6min and 76.4min respectively.

[0051] Comparative Example 3:

[0052] Weigh Zr, Nb and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Nb 0.2 Co alloy ingot. 0.8 Nb 0.2 The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Nb 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Nb 0.2 Co 2 alloy.

[0053] At room temperature, the activated dehydrogenated Zr 0.8 Nb 0.2 Co alloy introduced into 10 bar containing 2000 ppm CO 2 or H of CO 2 Mixed gas, measuring Zr 0.8 Nb 0.2 The kinetic curve of hydrogen absorption of Co in mixed gas. Figure 4 As shown, in H 2 +CO 2 and H 2 +CO mixed gas, the material can absorb 0.16wt% and 0.47wt% of hydrogen within 20min and 120min respectively.

[0054] Comparative Example 4:

[0055] Weigh Zr, Ti and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Ti 0.2Co alloy ingot. 0.8 Ti 0.2 The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Ti 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Ti 0.2 Co alloy.

[0056] At room temperature, the activated dehydrogenated Zr 0.8 Ti 0.2 Co alloy introduced into 10 bar containing 2000 ppm CO 2 or H of CO 2 Mixed gas, measuring Zr 0.8 Ti 0.2 The kinetic curve of hydrogen absorption of Co in mixed gas. Figure 5 As shown, in H 2 +CO 2 and H 2 +CO mixed gas, the material can absorb 0.13wt% and 0.33wt% of hydrogen within 20min and 120min respectively.

[0057] Comparative Example 5:

[0058] Weigh Zr, Co and Ni with an atomic ratio of 1:0.8:0.2 and perform magnetic levitation induction melting to obtain ZrCo with uniform composition. 0.8 Ni 0.2 Alloy ingot. The smelted ZrCo 0.8 Ni 0.2 The oxide film on the surface of the alloy was polished off with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar high-purity H 2 Hydrogen absorption for 10 hours to obtain activated hydrogen-absorbing ZrCo 0.8 Ni 0.2 H 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining the activated dehydrogenated ZrCo 0.8 Ni 0.2 alloy.

[0059] At room temperature, the activated dehydrogenated ZrCo0.8 Ni 0.2 Alloy introduced 10 bar containing 2000ppm CO 2 or H of CO 2 Mixed gas, measuring ZrCo 0.8 Ni 0.2 The hydrogen absorption kinetic curve in the mixed gas. Figure 6 As shown, in H 2 +CO 2 In the mixed gas, the material can absorb 0.16wt% hydrogen within 20min; 2 In the mixed gas of 100 % H2 + CO, the time required for the material to absorb 0.7 wt% hydrogen is 101.7 min.

[0060] Comparative Example 6:

[0061] Weigh Zr, Co and Cu with an atomic ratio of 1:0.8:0.2 and perform magnetic levitation induction melting to obtain ZrCo with uniform composition. 0.8 Cu 0.2 Alloy ingot. The smelted ZrCo 0.8 Cu 0.2 The oxide film on the surface of the alloy was polished off with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar high-purity H 2 Hydrogen absorption for 10 hours to obtain activated hydrogen-absorbing ZrCo 0.8 Cu 0.2 H 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining the activated dehydrogenated ZrCo 0.8 Cu 0.2 alloy.

[0062] At room temperature, the activated dehydrogenated ZrCo 0.8 Cu 0.2 Alloy introduced 10 bar containing 2000ppm CO 2 or H of CO 2 Mixed gas, measuring ZrCo 0.8 Cu 0.2 The hydrogen absorption kinetic curve in the mixed gas. Figure 7 As shown, in H 2 +CO 2 and H 2 +CO mixed gas, the material can absorb 0.04wt% and 0.24wt% of hydrogen within 20min and 120min respectively.

[0063] Embodiment 1:

[0064] Weigh Zr and Co with equal atomic ratios and perform magnetic levitation induction melting to obtain a ZrCo alloy ingot with uniform composition. The surface oxide film of the smelted ZrCo alloy is polished off with a grinding wheel, and then the ingot is placed in a reactor, dynamically evacuated at 500℃ for 1h, and then cooled to 100℃ for insulation. Then 20bar high-purity H 2 The activated ZrCoH was absorbed for 10 h. 3 powder.

[0065] The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550° C. and kept warm for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining an activated dehydrogenated ZrCo alloy.

[0066] The activated dehydrogenated ZrCo alloy was cooled to 430 °C in the furnace, and then 1.2 bar 95 mol% H 2 +5mol%N 2 or 95 mol% H 2 +5mol%CO 2 Mixed gas, keep warm for 5 / 10 / 15 / 30min. Next, the sample is cooled to room temperature under dynamic evacuation conditions to obtain a surface-modified ZrCo alloy sample.

[0067] At room temperature, 10 bar of 2000 ppm CO was introduced into the surface-modified ZrCo alloy sample. 2 H 2 Mixed gas, measure the hydrogen absorption kinetic curve of ZrCo in the mixed gas. Figure 8 , Fig. 9 As shown, with the 2 +N 2 or CO 2 The insulation modification time in the mixed gas was extended from 5min to 10min, 15min and 30min, and the sample's resistance to CO 2 The ability of poisoning gradually increases. 2 +CO 2 The hydrogen absorption rate in the mixed gas gradually increases. 2 +N 2 The sample (ZC-N) with surface modification for 10 min in the mixed gas has both high capacity and excellent anti-poisoning ability, and can absorb 1.9 wt% H in 40 s. 2 .like Fig.10 As shown, ZC-N samples are resistant to CO 2 and CO poisoning capabilities are significantly improved. 2 +CO 2 and H 2+CO mixed gas, the time required for the material to absorb 0.7wt% hydrogen is 0.1min and 7.1min respectively.

[0068] Embodiment 2:

[0069] Weigh Zr, Hf and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Hf 0.2 Co alloy ingot. 0.8 Hf 0.2 The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Hf 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Hf 0.2 Co alloy.

[0070] After activation, the dehydrogenated Zr 0.8 Hf 0.2 The Co alloy was cooled to 430°C in the furnace, and then 1.2 bar 95 mol% H 2 +5mol%N 2 Mixed gas, keep warm for 10 minutes. Next, the sample was cooled to room temperature under dynamic vacuum conditions to obtain surface-modified Zr 0.8 Hf 0.2 Co alloy sample (ZHC-N).

[0071] At room temperature, 10 bar of 2000 ppm CO was introduced into ZHC-N. 2 or H of CO 2 Mixed gas, measure its hydrogen absorption kinetic curve in the mixed gas. Fig.11 As shown, ZHC-N samples are resistant to CO 2 The poisoning ability of H 2 +CO 2 and H 2 +CO mixed gas, the time required for the material to absorb 0.7wt% hydrogen is 6.6min and 76.4min respectively.

[0072] Embodiment 3:

[0073] Weigh Zr, Nb and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Nb 0.2 Co alloy ingot. 0.8 Nb 0.2 The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Nb 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Nb 0.2 Co alloy.

[0074] After activation, the dehydrogenated Zr 0.8 Nb 0.2 The Co alloy was cooled to 430°C in the furnace, and then 1.2 bar 95 mol% H 2 +5mol%N 2 Mixed gas, keep warm for 10 minutes. Next, the sample was cooled to room temperature under dynamic vacuum conditions to obtain surface-modified Zr 0.8 Nb 0.2 Co alloy sample (ZNC-N).

[0075] At room temperature, 10 bar of 2000 ppm CO was introduced into ZNC-N. 2 or H of CO 2 Mixed gas, measure its hydrogen absorption kinetic curve in the mixed gas. Fig.12 As shown, ZNC-N samples are resistant to CO 2 The poisoning ability of H 2 +CO 2 and H 2 +CO mixed gas, the time required for the material to absorb 0.7wt% hydrogen is 2.7min and 47.9min respectively.

[0076] Embodiment 4:

[0077] Weigh Zr, Ti and Co with an atomic ratio of 0.8:0.2:1 and perform magnetic levitation induction melting to obtain Zr with uniform composition. 0.8 Ti 0.2 Co alloy ingot. 0.8 Ti 0.2The oxide film on the surface of the Co alloy was removed with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar of high-purity H 2 The activated hydrogen-absorbing Zr was obtained by absorbing hydrogen for 10 h. 0.8 Ti 0.2 CoH 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate and obtain the activated dehydrogenated Zr 0.8 Ti 0.2 Co alloy.

[0078] After activation, the dehydrogenated Zr 0.8 Ti 0.2 The Co alloy was cooled to 430°C in the furnace, and then 1.2 bar 95 mol% H 2 +5mol%N 2 Mixed gas, keep warm for 10 minutes. Next, the sample was cooled to room temperature under dynamic vacuum conditions to obtain surface-modified Zr 0.8 Ti 0.2 Co alloy sample (ZTC-N).

[0079] At room temperature, 10 bar of 2000 ppm CO was introduced into ZTC-N. 2 or H of CO 2 Mixed gas, measure its hydrogen absorption kinetic curve in the mixed gas. Fig.13 As shown, the ZTC-N sample is resistant to CO 2 The poisoning ability of H 2 +CO 2 In the mixed gas, the time required for the material to absorb 0.70wt% hydrogen is 5.6min; 2 +CO mixed gas, the material can absorb 0.56wt% hydrogen within 120min.

[0080] Embodiment 5:

[0081] Weigh Zr, Co and Ni with an atomic ratio of 1:0.8:0.2 and perform magnetic levitation induction melting to obtain ZrCo with uniform composition. 0.8 Ni 0.2 Alloy ingot. The smelted ZrCo 0.8 Ni 0.2 The oxide film on the surface of the alloy was polished off with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar high-purity H 2 Hydrogen absorption for 10 hours to obtain activated hydrogen-absorbing ZrCo 0.8 Ni0.2 H 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining the activated dehydrogenated ZrCo 0.8 Ni 0.2 alloy.

[0082] After activation, the dehydrogenated ZrCo 0.8 Ni 0.2 The alloy was cooled to 430°C in the furnace and then 1.2 bar 95 mol% H 2 +5mol%N 2 Mixed gas, keep warm for 10 minutes. Next, the sample was cooled to room temperature under dynamic vacuum conditions to obtain surface-modified ZrCo 0.8 Ni 0.2 Alloy sample (ZCN-N).

[0083] At room temperature, 10 bar of 2000 ppm CO was introduced into ZCN-N. 2 or H of CO 2 Mixed gas, measure its hydrogen absorption kinetic curve in the mixed gas. Fig.14 As shown, ZCN-N samples are resistant to CO 2 The poisoning ability of H 2 +CO 2 and H 2 +CO mixed gas, the time required for the material to absorb 0.7wt% hydrogen is 8.4min and 55.0min respectively.

[0084] Embodiment 6:

[0085] Weigh Zr, Co and Cu with an atomic ratio of 1:0.8:0.2 and perform magnetic levitation induction melting to obtain ZrCo with uniform composition. 0.8 Cu 0.2 Alloy ingot. The smelted ZrCo 0.8 Cu 0.2 The oxide film on the surface of the alloy was polished off with a grinding wheel, and then the ingot was placed in a reactor, dynamically vacuumed at 500°C for 1 hour, and then cooled to 100°C for insulation. Then 20 bar high-purity H 2 Hydrogen absorption for 10 hours to obtain activated hydrogen-absorbing ZrCo 0.8 Cu 0.2 H 3 The activated hydrogen-absorbing powder was placed in a reactor, and the reactor was heated to 550°C for 0.5 h under dynamic evacuation conditions to completely dehydrogenate, thereby obtaining the activated dehydrogenated ZrCo 0.8 Cu 0.2 alloy.

[0086] After activation, the dehydrogenated ZrCo 0.8 Cu 0.2 The alloy was cooled to 430°C in the furnace and then 1.2 bar 95 mol% H 2 +5mol%N 2 Mixed gas, keep warm for 10 minutes. Next, the sample was cooled to room temperature under dynamic vacuum conditions to obtain surface-modified ZrCo 0.8 Cu 0.2 Alloy sample (ZCC-N).

[0087] At room temperature, 10 bar of 2000 ppm CO was introduced into ZCC-N. 2 or H of CO 2 Mixed gas, measure its hydrogen absorption kinetic curve in the mixed gas. Fig.15 As shown, ZCC-N samples are resistant to CO 2 The hydrogen and CO poisoning capabilities are significantly improved, and the material can absorb 0.27wt% and 0.36wt% of hydrogen within 20min and 120min, respectively.

[0088] Embodiment 7:

[0089] The unmodified activated dehydrogenated ZrCo alloy and the ZrCo alloy in Example 1 were heated at 430°C and 1.2 bar 95 mol% H 2 +5mol%N 2 Samples nitrided for 10 min in mixed gas (ZC-N) and ZC-N samples containing 2000 ppm CO at 10 bar 2 H / CO 2 The samples saturated with hydrogen in the mixed gas (ZC-NH) were subjected to XRD tests, such as Fig.16 The main phase of the sample after nitridation modification is basically the same as that of the unmodified sample, both of which are BCC-ZrCo phase, indicating that nitridation modification mainly modifies the surface area of ​​ZrCo particles and does not affect the main phase structure of the material. The sample after surface modification contains 2000ppm CO at 10bar 2 H 2 The mixed gas absorbs hydrogen at room temperature and completely transforms into ZrCoH 3 phase, indicating that it can be used in H containing non-hydrogen impurity gases 2 The rapid absorption of hydrogen in the ZrCo alloy reaches saturation, which further proves the effectiveness of the present invention in enhancing the anti-poisoning ability of the ZrCo alloy.

[0090] Embodiment 8:

[0091] For ZrCo in Example 1, at 430°C, 1.2 bar, 95 mol% H 2 +5mol%N 2The sample nitrided in the mixed gas for 10 min (ZC-N) was characterized by transmission electron microscopy, such as Fig.17 As shown in Figure 2, a uniform and dense nitride protective layer is formed on the ZrCo surface after nitridation. This protective layer can prevent impurity gases from contacting the ZrCo surface and selectively transmit H 2 , thereby improving the material's anti-toxicity.

[0092] Embodiment 9:

[0093] For the unmodified ZrCo alloy, the ZrCo in Example 1 was heated to 430°C, 1.2 bar, 95 mol% H 2 +5mol%N 2 The sample (ZC-N) nitrided for 10 min in the mixed gas was subjected to the PCT test of hydrogen absorption / desorption, such as Fig.18 It can be seen that the PCT curve shape and hydrogen absorption / desorption plateau pressure of the modified sample are almost the same as those of the unmodified sample, indicating that the surface nitridation modification method described in the present invention will not affect the hydrogen absorption and desorption thermodynamic properties of the ZrCo-based alloy.

[0094] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. An in-situ surface modification method for enhancing the CO2 and CO poisoning resistance of high-density ZrCo metal-based hydrogen storage alloys, characterized in that: Includes steps: 1) Surface modification of the activated dehydrogenated ZrCo-based alloy in a H2+modifying gas mixture at 350-450°C; the modifying gas is at least one of N2 and CO2; 2) Under dynamic vacuum conditions, the alloy treated in step 1) is cooled to obtain a ZrCo-based alloy having CO2 and CO poisoning resistance.

2. The in-situ surface modification method according to claim 1, characterized in that: In step 1), the ZrCo-based alloy is a ZrCo alloy partially substituted or unsubstituted by one or more transition metal elements, and the transition metal elements are selected from Cu, Ni, Hf, Ti, and Nb.

3. The in-situ surface modification method according to claim 2, characterized in that: In step 1), the ZrCo-based alloy is ZrCo alloy, ZrCo (1-a) Cu a Alloy, ZrCo (1-b) Ni b Alloy, Zr (1-c) Hf c Co alloy, Zr (1-d) Ti d Co alloy or Zr (1-e) Nb e Co alloy, of which 0 <a<0.4,0<b<0.4,0<c<0.4,0<d<0.4,0<e<0.4。 4. The in-situ surface modification method according to claim 1, characterized in that: In step 1), an activated dehydrogenated ZrCo-based alloy is obtained by: The ZrCo-based alloy ingot is dynamically vacuumed at 400-500° C. to remove impurity gases on the surface of the ZrCo-based alloy ingot; after the vacuuming is completed, when the temperature is lowered to below 200° C., hydrogen is introduced to activate the surface degassed ZrCo-based alloy ingot by absorbing hydrogen, and then the temperature is raised to 500-550° C. to dynamically vacuum dehydrogenate the hydrogen-absorbed and activated ZrCo-based alloy to obtain the activated dehydrogenated ZrCo-based alloy.

5. The in-situ surface modification method according to claim 1, characterized in that: In step 1), the temperature at 350-450° C. is kept for 3-30 minutes.

6. The in-situ surface modification method according to claim 1, characterized in that: In step 1), the initial back pressure of the introduced H2+ modified gas mixture is 0.5-4.0 bar.

7. The in-situ surface modification method according to claim 1, characterized in that: In step 1), the content of the modified gas in the H2+ modified gas mixture is 1 mol%-10 mol%.

8. A ZrCo-based alloy having CO2 and CO poisoning resistance, characterized in that: The method is prepared by the in-situ surface modification method according to any one of claims 1 to 7.

9. Use of the ZrCo-based alloy having resistance to CO2 and CO poisoning according to claim 8 in the storage, supply and recovery of hydrogen isotopes.

10. The use according to claim 9, characterized in that: The hydrogen isotopes include one or more of protium, deuterium and tritium.

Citation Information

Patent Citations

  • Method for enhancing carbon dioxide poisoning resistance of ZrCo alloy

    CN116288081A

  • New solid crystalline porous metal organic framework with modified surface, useful as medical imaging marker, a medicament and as a contrast agent, comprises three-dimensional units

    FR2921661A1